ON THE TEACHABILITY OF COMMUNICATION STRATEGIES TO JORDANIAN EFL BEGINNERS: EXPLORATION AND REFLECTION - Ruba Fahmi Bataineh; Wedad Khalid Al-Bzour; Abdallah Ahmad Baniabdelrahman (Informascope, 2017)
This study examines the effect of communication strategy instruction on Jordanian EFL students' oral performance and strategy use.  Following a thorough content analysis of units 10- 13 of the prescribed Action Pack textbook, the instructional material was designed and implemented over a duration of eight weeks.  A three-task oral pre-/ post-test, a communication strategies-based observation checklist, and a 10-item scoring rubric were used to collect data from a purposeful sample of 24 sixth-grade students. The (predominantly interactional) communication strategies of approximation, circumlocution, repetition, appeal for help, self-repair, appeal for confirmation, appeal for clarification, and guessing were targeted.  The data analysis, both quantitative and qualitative, suggests that the utilization of communication strategies in language instruction both improves oral performance and increases strategy use. Keywords: communication strategies, EFL, oral performance, strategy instruction